Contributions of climate, plant phenology and natural enemies to the seasonal variation of aphids on cabbage. (8th January 2019) - Fidelis, Elisangela G.; Farias, Elizeu S.; Lopes, Mayara C.; Sousa, Fernanda F.; Zanuncio, José C.; Picanço, Marcelo C.
Abstract: Brevicoryne brassicae (L), Lipaphis erysimi (Kalt) and Myzus persicae (Sultzer) (Homoptera: Aphididae) form the aphid complex that causes great losses in Brassicaceae in tropical and subtropical regions. Knowledge of their population dynamics is important for the development of integrated pest management programmes. This study aimed to investigate the effects of cabbage phenology, climatic factors and natural enemies populations on the dynamics of these organisms, and the factors regulating their predators' occurrence. The densities of aphids and their natural enemies and the climate were monitored for two years in 16 cabbage crops. The highest densities of the aphids occurred during periods of relative humidity (RH) drop, a condition that affects them positively. Regarding the predators, the factors affecting their abundance varied but RH was positively related to most of them. This study provides relevant insights into the factors that regulate the aphids in cabbage and for the decision‐making process of control of these severe pests.